2012
DOI: 10.2141/jpsa.011071
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Behavioral Responses of Young Chicks to High Ambient Temperature

Abstract: Birds reduce their food intake by the exposure to high ambient temperature (HT) which ultimately affects their productivity. However, physiological and behavioral responses of young chicks of different ages to HT have not yet been investigated. In this study, we examined the effects of HT (40℃, 4-h) in 3-, 5-, 7-, 14-and 21-d old chicks. There were no significant differences in food intake between heat exposed and control chicks up to 7-d old, while clear suppressions of food intake were observed in 14-and 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…Food (Commercial starter diet (metabolisable energy: 12.77 MJ/kg and protein: 24%; food ingredients: grain 61% (mainly maize), defatted meal 25% (soybean meal and maize gluten meal), fish meal 9%, rice bran 1% and others 4%; AX; Toyohashi Feed and Mills Co. Ltd., Aichi, Japan)) and water were available ad libitum. On the basis of our previous experiment, 14-or 21-d-old chicks were more responsive to HT in terms of food intake than neonatal chicks (Chowdhury et al, 2012b). Thus, in the present study, we used 14-d-old chicks to examine the effect of HT (35°C) in comparison with that of a control thermoneutral temperature (CT; 30°C).…”
Section: Experimental Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Food (Commercial starter diet (metabolisable energy: 12.77 MJ/kg and protein: 24%; food ingredients: grain 61% (mainly maize), defatted meal 25% (soybean meal and maize gluten meal), fish meal 9%, rice bran 1% and others 4%; AX; Toyohashi Feed and Mills Co. Ltd., Aichi, Japan)) and water were available ad libitum. On the basis of our previous experiment, 14-or 21-d-old chicks were more responsive to HT in terms of food intake than neonatal chicks (Chowdhury et al, 2012b). Thus, in the present study, we used 14-d-old chicks to examine the effect of HT (35°C) in comparison with that of a control thermoneutral temperature (CT; 30°C).…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Behavioural, physiological and molecular adjustments occur when chickens are exposed to heat stress (Etches et al, 1995). In our previous report, it was shown that young chicks, when exposed to HT, reduced their food intake and that the expression of a food intake-regulating hypothalamic neuropeptide mRNA increased (Chowdhury et al, 2012b). Balnave and Oliva (1991) showed that the absorption of arginine, an essential amino acid in chickens, decreased significantly during HT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is attributed to the fact that newborn chicks are poikilothermic, due to their not yet developed thermoregulatory mechanisms (Mujahid, 2010). As a result, chicks are particularly sensitive to thermal environments outside their comfort range (Moura et al, 2008;Mujahid & Furuse, 2009;Chowdhury et al, 2012). Broilers achieve the best performance when reared in thermoneutral conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Data on the thermal comfort for chicks have been commonly cited in the literature, showing that both heat and cold stress can cause reduced growth rate, body mass loss, and other damage to the health, and expression of anomalous behaviour of chicks during the first three weeks of life (Mujahid & Furuse;2009;Chowdhury et al, 2012). Damages occur because broiler growth rate is sensitive to extreme environmental temperatures (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%